Diplomasi Digital dan Pembangunan Berkelanjutan: Tinjauan Literatur Semantik tentang Inklusivitas, Kebijakan, dan Teknologi - Asrudin; Triwahyuni, Dewi; Nurrahman, Diyat (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2025)
This article examines the intersection of digital diplomacy, artificial intelligence (AI), and sustainable development using a Literature Semantic Review (LSR) approach. By analyzing ten peer-reviewed journal articles published between 2014 and 2024, this study explores how digital diplomacy contributes to the Sustainable Development Goals (SDGs), particularly in terms of inclusivity, governance, and technology. The methodology combines the PRISMA framework for systematic literature selection with semantic analysis tools such as NVivo to map conceptual relationships. The results highlight that key concepts—digital diplomacy, AI, inclusivity, policy, and technology—are strongly interconnected in shaping global diplomatic practices. Notably, the study reveals a lack of representation of developing countries in existing literature and emphasizes the need for inclusive digital policies. The conclusion proposes a conceptual model of inclusive digital diplomacy that integrates technological innovation, ethical governance, and broader participation of marginalized groups. This model supports the development of fair and effective digital diplomacy strategies aligned with global sustainability goals.